Pembaharuan Hukum Pidana; Konsep Pertanggungjawaban Pidana Dalam Hukum Pidana Nasional Yang Akan Datang - Septa Candra (Jurnal Cita Hukum, 2013)
Concept of Criminal Liability in the Future of National Criminal Law. Separating criminal offense and libility would create a more comprehensive and systematic order towards penal code. This dualistic view implied that the formulation of criminal law only contain actus reus as an objective elements, while mens rea becomes the elements of criminal offense. The view also affect the liability concept. Based on this conception, the future national criminal law would be based on the actions and the doers (daad-dader-strafrecht). DOI: 10.15408/jch.v1i1.2979